Torsional Wave Propagation in Sandwich Hollow Cylinder With Pre-Strained Face (Core) Layers (Layer) - Akbarov, S. D.; Kepceler, T.; Egilmez, M. Mert; Dikmen, F. (TRANS TECH PUBLICATIONS LTD, 2012)
This paper studies torsional wave dispersion in a three-layered (sandwich) hollow cylinder with pre-strained face (core) layers (layer) made from high elastic materials the mechanical relations of which are described through the harmonic potential. The investigations are carried out within the scope of the piecewise homogeneous body model with the use of the three-dimensional linearized theory of elastic waves in initially stressed bodies. The analytical expression is obtained for the low wave number limit values of the torsional wave propagation velocity. The numerical results on the influence of the initial strains of the face (core) layers (layer) of the cylinder on the torsional wave propagation velocity are presented and discussed.
Keywords: Initial strains; wave dispersion; three-layered hollow cylinder; high elastic material; torsional wave; MATERIAL COMPOUNDED CYLINDER; CIRCULAR-CYLINDER; DISPERSION RELATIONS; Engineering; Materials Science